COMPARISON OF HOSPITALIZATION EVENTS AND ESTIMATION OF HAZARD RATIO FOR PATIENTS WITH HYPERTENSIVE EMERGENCIES AND HYPERTENSIVE URGENCIES AFTER 12 MONTH FOLLOW UP A GREEK REGISTRY. (April 2021) - Fragoulis, C.; Tsioufis, K.; Tzorovili, E.; Dimitriadis, K.; Siafi, E.; Leontsinis, I.; Konstantinidis, D.; Kakouri, N.; Nihoyannopoulos, P.; Tousoulis, D.
Abstract : Objective: The purpose of our registry was to record the prevalence and clinical characteristics of patients with hypertensive urgencies (HU) and emergencies (HE) assessed in the emergency department (ED) and during hospitalizationand a 12 month follow-up to record new events in a Greek General Hospital. Design and method: The study population consisted of patients presenting at the emergency department with acute increase in blood pressure (BP)(systolic BP > or = 180mmHg and/or diastolic BP > or = 120mmHg) and depending on the presence or absence of acute hypertension-mediated target organ damage, participants weredivided into the HE and the HU group, respectively. In all patients the demographic andclinical parameters were recorded for 12 monthsand there was a 12 month follow-up for new hospitalizations. Results: Out of 38, 589 patients assessed in the ED during a period of 12 months, 353 (0.91%) had HU and HE, out of which 256 (72.5%) hadHU and 97 (27.5%) had HE. The mean age of patients was 67.4 ± 12.9years, 49% were males and 80% had history of hypertension. Patients with HE compared to HU were older (72.7 ± 12.1 vs 61.4 ± 12.7years, p < 0.0001). At baseline 91 patients with HE and 25 with HU were admitted in the hospital and remained for 6.4 ± 5.6days. During the study period82 patients were excluded for not completing the follow-up. Comparing the 2 groups, 51 patients from HE and 39 from HUgroup were hospitalized (p < 0.0001, HR for HE 2.3, 95% CI 1.5–3.7). 29patients from HE and 9 from HU group were hospitalized for cardiovascular disease (p < 0.0001, HR for HE 3.8, 95%CI 1.7–8.6). 32 patients from HE and 34 from HU group were hospitalized for non cardiovascular disease (p < 0.05, HR for HE 1.7, 95% CI 1.02–3.02). Cox regression models were adjusted for age, gender, cardiovascular disease, chronic kidney disease, heart failure and diabetes mellitus. Conclusions: Our registry emphasizes the elevated hazard ratio for hospitalizations in the group of HE compared with HU, the necessity for more intensive follow-up for the first group and the need for further research in this setting.